Perbedaan Tingkat Stres Berdasarkan PSS pada Mahasiswa Tingkat 1 dengan Tingkat 3 Tahun Ajaran 2020-2021 Fakultas Kedokteran Unisba Selama Pembelajaran di Masa Pandemi COVID-19 - Fannisa Wiguna; Budiman; Rika Nilapsari (UNISBA Press, 2022)
Abstract. In the learning process to become a doctor, medical students face various kinds of demands that cause stress, especially during the COVID-19 pandemic which tends to increase the perception of stress and affect the mental health of both early and final year students. This study aims to determine the difference in stress levels based on PSS-10 in level 1 students and level 3 students of the Faculty of Medicine, Islamic University of Bandung during learning during the COVID-19 pandemic. This research is quantitative, analytical observational with a cross sectional study design with research samples of students from the Faculty of Medicine, Bandung Islamic University, level 1 and level 3 for the 2020-2021 academic year. The results of this study will be analyzed statistically with the Chi-Square test. In this study, it was found that level 1 students of the Faculty of Medicine, Islamic University of Bandung in the academic year 2020-2021 the most experienced moderate levels of stress (33.5%) as well as level 3 students of the Faculty of Medicine, Islamic University of Bandung the most experienced moderate levels of stress. (29.3%) and there is a difference in the level of stress in level 1 and level 3 students. The same result was also found that the level of stress was higher in level 3 students with a P value (P = 0.01).In this study it can be concluded that level 1 and level 3 students of the Faculty of Medicine, Islamic University of Bandung for the academic year 2020-2021 experience the most moderate stress and stress level 3 students have higher stress levels than level 1 students. Abstrak. Dalam proses pembelajaran menjadi seorang dokter, mahasiswa kedokteran menghadapi berbagai macam tuntutan yang menyebabkan stres terutama pada masa pandemi COVID-19 yang cenderung meningkatkan persepsi stres dan mempengaruhi kesehatan mental baik mahasiswa tingkat awal dan tingkat akhir. Penelitian ini bertujuan mengetahui perbedaan tingkat stres berdasarkan PSS-10 pada mahasiswa tingkat 1 dan mahasiswa tingkat 3 Fakultas Kedokteran Universitas Islam Bandung selama pembelajaran di masa pandemi COVID-19.Penelitian ini bersifat kuantitatif, observasional analitik dengan rancangan studi cross sectional dengan sampel penelitian mahasiswa Fakultas Kedokteran Universitas Islam Bandung tingkat 1 dan tingkat 3 tahun ajaran 2020—2021. Hasil dari penelitian ini akan dianalisis secara statistik dengan Chi-Square test. Pada penelitian ini didapatkan hasil bahwa mahasiswa tingkat 1 Fakultas Kedokteran Universitas Islam Bandung tahun ajaran 2020—2021 paling banyak mengalami tingkat stres sedang (33,5%) begitu pun dengan mahasiswa tingkat 3 Fakultas Kedokteran Universitas Islam Bandung paling banyak mengalami tingkat stres sedang (29,3%) dan terdapat perbedaan tingkat stres pada mahasiswa tingkat 1 dan tingkat 3.Hasil yang sama juga didapatkan bahwa tingkat stres lebih tinggi pada mahasiswa tingkat 3 dengan nilai P (P=0,01).Dalam penelitian ini dapat disimpulkan bahwa mahasiswa tingkat 1 dan tingkat 3 Fakultas Kedokteran Universitas Islam Bandung tahun ajaran 2020—2021 paling banyak mengalami stres sedang dan stres pada mahasiswa tingkat 3 tingkat stres lebih tinggi daripada mahasiswa tingkat 1.